Modern universities in a digital environment - Miklós Lukovics; Bence Zuti (15th International Scientific Days ,,Challenges and Prospects for Innovation between 2014-2020”, 2016)
Nowadays the digitalization of all aspects of our lives is becoming more and more general. This pattern is also true in case of modern institutions of higher education. In case of the operation of universities, we can identify a shift towards a growingly increasing approach, which is proactive strategic thinking done by university management. Many successful examples throughout the globe prove that universities may positively affect the level of economic development in given regions. This can happen with the collective presence of three key activities carried out by these institutions. Excellent education, successful research and embedment in the local economy are all necessary activities. It is recognized that without a proper knowledge management system, universities are less competitive. They need to possess outstanding IT-infrastructures, large databases and host professional forums that can enhance knowledge transfer. Thus, knowledge management and a vision for digitalization in the everyday lives of universities should be considered as an integral and inevitable part of university strategies. The study has two goals: It attempts to identify, how digitalization can contribute to the excellence of the first mission of universities and also examines the role of modern universities in activities that can enhance knowledge-transfer.
Keywords: I20; I25; O30; 330; knowledge management; third mission; modern universities; digitalization